Adaptive magnetic resonance image guided radiation for intact localized prostate cancer how to optimally test a rapidly emerging technology - Hall, William A.; Kishan, Amar U.; Hall, Emma; Nagar, Himanshu; Vesprini, Danny; Paulson, Eric; Van der Heide, Uulke A.; Lawton, Colleen A. F.; Kerkmeijer, Linda G. W.; Tree, Alison C. (Frontiers in Oncology, 2022)
Introduction: Radiation therapy (RT) provides an excellent management option for prostate cancer with high rates of control and low toxicity. Historically RT has been given with CT based image guidance. Recently, magnetic resonance (MR) imaging capabilities have been successfully integrated with RT delivery platforms, presenting an appealing method of adapting and guiding RT. We sought to summarize optimal strategies to test the benefits of MR guidance specifically in localized, intact prostate cancer. Methods: Radiation oncologists, physicists, and statisticians were identified to collectively address this topic. Participants had a clinical focus on using MR guidance and prospective randomized trials in localized prostate cancer. The goal was to review both published and ongoing trials, along with develop and proposing novel trials for future consideration. Trial hypotheses, endpoints, and areas for improvement in localized prostate cancer that specifically leverage MR guided technology are presented. Results: Over 10 prospective trials were found that explored the potential of adaptive MRI-guided radiotherapy in the definitive treatment of prostate cancer. Different primary areas of improvement that MR guidance may offer in prostate cancer were summarized. Clinical trial design strategies are presented that summarize different options for clinical trials testing the potential benefits of MRI-guided RT. Conclusions: The number and scope of trials evaluating MRI-guided RT for localized prostate cancer is limited. Yet multiple promising opportunities to test this technology and potentially improve outcomes for men with prostate cancer undergoing definitive RT exist. Attention, in the form of multi-institutional randomized trials, is needed.